Reka bentuk dan pembangunan perisian kursus multimedia pendidikan seksualiti Malaysia (MSE) - Azizah Jaafar; Chan, Siew Lee (penerbit ukm, 2009)
The government of Malaysia has introduced the National Sexuality Education Guideline in 2006 to overcome social problems amongst the juveniles. An early study related to the perception of teachers and students toward the sexual education curriculum taught in schools currently was carried out. The study showed that there is a big gap between the perception of the students and teachers towards several issues, such as resources, and content adequacy of Malaysia Sexuality Education (MSE) today. The theoretical framework of MSE was designed and developed based on several learning theories, and human computer interactive theories to handle the sensitive sexuality issues of the Malaysian community especially the students. The theoretical framework was executed through a comprehensive research methodology as the model ADDIE is integrated with usage-centered design to achieve high usability courseware. In conclusion, the MSE courseware will be a tool or product to be used as a solution to teaching and learning problems in MSE.